Antibody responses to SARS-CoV-2 vaccines in 45,965 adults from the general population of the United Kingdom - Wei, J; Stoesser, N; Matthews, P; Ayoubkhani, D; Studley, R; Bell, I; Bell, J; Newton, J; Farrar, J; Diamond, I; Rourke, E; Howarth, A; et al. (Springer Nature, 2021)
We report that in a cohort of 45,965 adults, who were receiving either the ChAdOx1 or the BNT162b2 SARS-CoV-2 vaccines, in those who had no prior infection with SARS-CoV-2, seroconversion rates and quantitative antibody levels after a single dose were lower in older individuals, especially in those aged >60 years. Two vaccine doses achieved high responses across all ages. Antibody levels increased more slowly and to lower levels with a single dose of ChAdOx1 compared with a single dose of BNT162b2, but waned following a single dose of BNT162b2 in older individuals. In descriptive latent class models, we identified four responder subgroups, including a ‘low responder’ group that more commonly consisted of people aged >75 years, males and individuals with long-term health conditions. Given our findings, we propose that available vaccines should be prioritized for those not previously infected and that second doses should be prioritized for individuals aged >60 years. Further data are needed to better understand the extent to which quantitative antibody responses are associated with vaccine-mediated protection.